PROBABILITY ASSESMENT OF CORRECT ADR VEHICLE LABELLING USING BAYESIAN STATISTICS (Perner's Contacts, 2013)
This article is focused on theoretical and mathematical assessment of the probability of correct labelling of vehicles transporting dangerous goods according to the international ADR agreement. The calculations used the principles of Bayesian statistics and general knowledge of the theory of probability. For the mathematical part of the solution were used statistical data on the transport of dangerous goods in the Czech Republic. In conclusion there are suggested possible links and implications of the findings.